Protective role of Nigella sativa oil against cisplatin-induced ototoxicity: a literature review - Donny Hendriyanto; Helmi Helmi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Cisplatin is widely used for the chemotherapy of head and neck cancer. However, it has a significant ototoxicity. Nigella sativa has been scientifically proven to have numerous benefits included to prevent adverse effect of a drug. This literature review aimed to evaluate the protective role of N. sativa oil against cisplatin-induced ototoxicity. Relevant publications were searched  from PubMed and Google Scholar databases within the last 10 years. Ototoxicity due to cisplatin can occur through the intrinsic and extrinsic pathways. Cisplatin causes endoplasmic reticulum stress, DNA damage, increased reactive oxygen species (ROS) and inflammatory processes, resulting in increased apoptosis of cochlear outer hair cells. The active constituents of N. sativa including flavonoids, phenolics and thymoquinone can prevent the cisplatin-induced ototoxicity. Examination of endogenous antioxidants, antiapoptotic, and proinflammatory could be used as primary approach to evaluate the protective role of N. sativa against cisplatin-induced ototoxicity.